Lactose absorption in patients with glucose 6-phosphate dehydrogenase deficiency with and without favism. Issue 2 (August 1996) - Meloni, T; Colombo, C; Ogana, A; Mannazzu, M C; Meloni, G F
Abstract : BACKGROUND: It has recently been suggested that primary lactase deficiency might have been selected for by malaria, as has been previously shown to occur for thalasaemia and glucose 6-phosphate dehydrogenase (G6PD) deficiency. AIMS: To test this hypothesis, the prevalence of primary lactase deficiency in G6PD deficient subjects and in controls from the area of Sassari (Northern Sardinia) was determined, which in the past was characterised by an intermediate malarial endemicity. SUBJECTS: 70 adult subjects with G6PD deficiency, 34 of whom had a past history of favism, and 50 age matched control subjects. METHODS: The capacity to absorb lactose was assessed by measuring breath hydrogen production after oral administration of lactose (50 g) by a gas chromatographic method. RESULTS: Twenty per cent of G6PD deficient subjects with a positive history of favism and 22% of G6PD deficient subjects without a positive history of favism were lactose absorbers compared with 14% lactose absorbers in the control group. The differences were not statistically significant. CONCLUSIONS: These data show that the prevalence of primary lactase deficiency in the area of Sassari is relatively high, but comparable to that seen in the adult population from another area of southern Italy (Naples) where malaria was less endemic.